THE INFLUENCE OF WORK MOTIVATION, WORK DISCIPLINE ON EMPLOYEE PERFORMANCE (CASE STUDY AT MERANGIN REGENCY SETTLEMENT AREA OFFICE EMPLOYEES) - Mardalena; Sarinah; Endang Solichin (Dinasti Publisher, 2020)
This research aims to determine the effect of work motivation and work discipline on employee performance partially and simultaneously at the same time. The type of research used is explanatory research with a quantitative approach. The sample of this study were employees at the Merangin Regency Resettlement Area Office. Number of sample were 80 person. Data obtained by distributing questionnaires. The data analysis technique used in this study is multiple linear regression analysis, using the F test and T test. The results of multiple linear regression Y = 79.21 + 0.41 X1 + 0.74 X2 + e. Meanwhile the results of the T test of work motivation variables on employee performance are t count ? t table or 3.31 ? 1.99. while, work discipline variable on employee performance was t count ? t table or 5.02 ? 1.99. The coefficient of determination (R2) is 0.34%. This means that 34% of the variation in performance can be predicted by work motivation and work discipline variables. While 65% can be predicted by other variables.